2021
DOI: 10.1098/rsif.2021.0570
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to inhibitory signals changes as a function of colony size in honeybees ( Apis mellifera )

Abstract: Biological collectives, like honeybee colonies, can make intelligent decisions and robustly adapt to changing conditions via intricate systems of excitatory and inhibitory signals. In this study, we explore the role of behavioural plasticity and its relationship to network size by manipulating honeybee colony exposure to an artificial inhibitory signal. As predicted, inhibition was strongest in large colonies and weakest in small colonies. This is ecologically relevant for honeybees, for which reduced inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In agreement with field observations of honeybees, which increase stop signalling when a quick response is necessary [ 10 ], our analysis also predicts a speed-up of the group dynamics for higher levels of negative feedback. The dynamics of Fig 3 can also be discussed in light of the results of a recent empirical study which has found that sensitivity to inhibitory signalling changes as a function of colony size [ 34 ]. Our model, by linking the negative feedback rate with convergence speed and the deviation from the target distribution, offers predictions that can be tested on colonies of different sizes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In agreement with field observations of honeybees, which increase stop signalling when a quick response is necessary [ 10 ], our analysis also predicts a speed-up of the group dynamics for higher levels of negative feedback. The dynamics of Fig 3 can also be discussed in light of the results of a recent empirical study which has found that sensitivity to inhibitory signalling changes as a function of colony size [ 34 ]. Our model, by linking the negative feedback rate with convergence speed and the deviation from the target distribution, offers predictions that can be tested on colonies of different sizes.…”
Section: Resultsmentioning
confidence: 99%
“…Our model, by linking the negative feedback rate with convergence speed and the deviation from the target distribution, offers predictions that can be tested on colonies of different sizes. For example, the time to adaptation to environmental changes is expected to be longer in smaller colonies, where bees show a lower sensitivity to inhibitory signalling [ 34 ], than in larger colonies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hornstein et al (2021) suggested that this may be explained by the fact that social support figures often do not prevent the occurrence of fearful incidents but instead they modulate the capacity to "cope" with emotional challenges. With regard to the origin of the features exhibited by social support cues, the authors propose that they are "prepared," which in this context means that they are acquired by means other than Pavlovian conditioning (for an example of a prepared inhibitory social signal in the appetitive domain, see Bell et al, 2021). Hornstein et al (2021) urged other researchers to pursue studies examining the route by which social support figures acquire fear suppression properties or assessing the possibility that those properties are innate.…”
Section: Some Psychiatric Conditions As Deficits or Excesses In Inhib...mentioning
confidence: 99%